Pendekatan Hukum Audit Klinis dan Sanksi di Fasilitas Pelayanan Kesehatan Indonesia: Mengutamakan Keadilan, Kepastian Hukum, dan Kemanfaatan - Sadnyini, Ida Ayu; Christianto, David; Kurniawan, I Gede Agus; Jayantara, Made (Jurnal MHKI, 2023)
Laws in Indonesia ensure that everyone has the right to safe, high-quality, and affordable health services. Health Service Facilities are required to have effective management and governance systems according to Article 21 of Law No. 36 of 2009 on Health. However, regulations regarding clinical audits, which aim to reduce negligence risks in healthcare facilities, and the process and sanctions for unintended errors in patient care remain unclear. This study employed empirical legal research and found that the regulation of clinical audits needs an approach based on justice, legal certainty, and usefulness to effectively reduce negligence risks in healthcare facilities. The audit process and imposition of sanctions for unintended errors in patient care can lead to civil and criminal lawsuits. In conclusion, clinical audits in Indonesia should prioritize the principles of justice, legal certainty, and usefulness to mitigate negligence risks in healthcare facilities. Fair and proportional sanctions should be applied, with a focus on improving the qualifications of healthcare workers, enhancing systems, and developing policies for better healthcare services. Patients should have the right to claim compensation and file complaints both civilly and criminally.